Effect of Stray and High Voltage Exposure on Livestock: An Overview (Indian Journal of Animal Production and Management, 2024)
Electricity is essential to dairy farming and  electrically powered machines are used for milking,  automatic feed dispensers and heated water bowls.  Leakage of current from these equipments, high  voltage lines or faulty connections between the  electrical circuit and the earth can lead to an  undesirable electrical phenomenon called stray  voltage. Stray voltage is a small voltage ( 6  mA (up to 10): Feed intake is reduced, resulting in  lower meat and milk production. Common  symptoms of stray voltage in cows include  hesitation to enter the parlor, they may stampede or  rush out of the parlor when released, cows dance  or step around constantly while in the milking parlor,  Normal milk letdown is interrupted, Increased  milking time, Udder irritation caused by residual  milk and increased somatic cell count which  increases the incidence of mastitis.
Keywords: stray voltage; electrical exposure; mastitis; somatic cell count